Improvement of training process of powerlifters on the basis of an interactive program "PersTrainer" - Volodymyr Ashanin; Anatoliy Rovnyi; Vladlena Pasko; Maksim Voitenko (Kharkiv State Academy of Physical Culture, 2017)
Purpose: to develop and scientifically substantiate the program "PersTrainer" for improving the training process of powerlifters. Material & Methods: the study involved the powerlifters of 16-18 years. The following research methods were used: analysis and generalization of the literary sources and data of the Internet, pedagogical observation and the method of information modeling. Results: the interactive program "PersTrainer" is developed and theoretically justified, which allows individually calculating the training load in different training cycles. Conclusion: it is possible to plan training loads on the basis of individually proposed exercise complexes, which are presented in the interactive program "PersTrainer".